An Assessment of the Impacts of Inadequate Housing on the Health of Urban Dwellers: A Case Study of Bweyale Town Council of Kiryandongo District - Malaki, Wanjala (Kabale University, 2019)
A Research Report Submitted to the Department of Environment and Natural Resources in Partial Fulfillment for the Award of Bachelors of Environment Science of Kabale University